Ganglioneuroblastoma: Unusual presentation as a pleural mass mimicking mesothelioma - Jain, Bhawna Bhutoria (Lung India, 2016)
Ganglioneuroblastoma (GNB) is a rare peripheral neuroblastic tumor that is derived from developing neuronal cells of the sympathetic nervous system, and usually occurs in young children. We present a case of GNB occurring as pleural mass in a 2-year-old boy, which led to diagnostic confusion. On fine-needle aspiration cytology (FNAC), it was misinterpreted as mesothelioma. He underwent thoracotomy with excision of the mass. Histopathological findings showed features of a biphasic tumor suggestive of mesothelioma. Immunohistochemistry (IHC) performed for mesothelioma markers were inconclusive. On review of the histology slides, GNB was considered, which was subsequently proven by IHC. The rarity of this tumor, along with its nearly restricted occurrence at a young age, necessitates a strong suspicion in patients presenting with a symptomatic intrathoracic mass.